Characterization of blue-green blood leukocyte inclusions and accompanying clinical, hematologic, and serum biochemical changes in dogs - Sebastian, Kimberley N (Veterinary clinical pathology, 2024)
© 2024 The Authors. Veterinary Clinical Pathology published by Wiley Periodicals LLC on behalf of American Society for Veterinary Clinical Pathology.